Inquiry Learning Model Assisted by Educational Games on Students’ Computational Thinking Skills - Ni Luh Nyoman Anggareni Julianti; Gusti Ngurah Sastra Agustika; Adrianus I Wayan Ilia Yuda Sukmana (Indonesian Journal of Instruction, 2026)
Computational thinking is a key 21st century skill that plays an important role in helping students solve problems logically, systematically, and in a structured manner. Learning practices that are still dominated by conventional and teacher-centered approaches have caused this skill to develop less optimally. This study aimed to analyze the effect of implementing an inquiry learning model assisted by educational games on fifth grade students’ computational thinking skills in mathematics learning. This study employed a quantitative approach with a quasi-experimental design using a nonequivalent pretest-posttest control group design. The research subjects consisted of 40 fifth grade students who were divided into an experimental group and a control group, with 20 students in each group. Data were collected through pretest and posttest using an instrument consisting of 15 multiple choice questions developed based on the dimensions of computational thinking, namely decomposition, pattern recognition, abstraction, and algorithms. The data were analyzed using inferential statistics through prerequisite tests and hypothesis testing. The findings showed that students who participated in learning through the inquiry learning model assisted by educational games demonstrated a better improvement in computational thinking skills compared to those who received conventional instruction. The conclusion of this study indicates that the model is effective in developing students’ computational thinking skills. The implication is that this model can be used as an alternative learning strategy to strengthen higher order thinking skills in mathematics learning.